The Importance of Timing in Segregated Theta Phase-Coupling for Cognitive Performance - Polanía, Rafael; Nitsche, Michael A.; Korman, Carolin; Batsikadze, Giorgi; Paulus, Walter (Current biology, 2012)
Functional cortical circuits for central executive functions have been shown to emerge by theta (∼6 Hz) phase-coupling of distant cortical areas [1–3]. It has been repeatedly shown that frontoparietal theta coupling at ∼0° relative phase is associated with recognition, encoding, short-term retention, and planning [1, 4, 5]; however, a causal link has not been demonstrated so far. Here we used transcranial alternating current stimulation [6–8] simultaneously applied at 6 Hz over left prefrontal and parietal cortices with a relative 0° (“synchronized” condition) or 180° (“desynchronized” condition) phase difference or a placebo stimulation condition, whereas healthy subjects performed a delayed letter discrimination task. We show that exogenously induced frontoparietal theta synchronization significantly improves visual memory-matching reaction times as compared to placebo stimulation. In contrast, exogenously induced frontoparietal theta desynchronization deteriorates performance. The present findings provide for the first time evidence of causality of theta phase-coupling of distant cortical areas for cognitive performance in healthy humans. Moreover, the results demonstrate the suitability of transcranial alternating current stimulation to artificially induce coupling or decoupling of behaviorally relevant brain rhythms between segregated cortical regions. ► Frontoparietal theta de/synchronization slows/speeds working memory matching ► Causality for timing-dependent theta phase-coupling in cognitive performance ► Coupling/decoupling of brain rhythms between cortical regions may be feasible with tACS